LIFE AFTER BONE MARROW TRANSPLANT: IMPLICATIONS FOR DAILY ROUTINES - Angélica Mônica Andrade; Edna Aparecida Barbosa de Castro; Kelli Borges dos Santos; Teresa Cristina Soares (Universidade Federal do Paraná, 2012)
This qualitative study sought to understand the experiences of adults who had submitted to autologous bone marrow transplant and to identify the implications for daily routines in the individuals who had gone through it. Interviews were undertaken, guided by a semi-structured script, with seven adult inpatients who had undergone the transplant, in a country town in the state of Minas Gerais, and who had been discharged between October 2004 and September 2010. Evidence was found for questions relevant to implications for daily routines of the people, with changes in life after the bone marrow transplant. After thematic content analysis, three empirical categories emerged: Withdrawal from work; Sleeplessness: Constant worry about relapses after discharge and Restructuring of one's life after bone marrow transplant - redefining existing. It is concluded that it is necessary to incorporate thoroughly adaptive professional conduct, using different strategies such as creativity, emotion and, above all, scientific knowledge.